TRANSPARENCY OF VILLAGE FINANCIAL MANAGEMENT TO THE COMMUNITY (Case Study of Ketupat Village, Raas District, Sumenep Regency): TRANSPARENCY OF VILLAGE FINANCIAL MANAGEMENT TO THE COMMUNITY - syahril; Fatmawati; Alwiyah; Faizul Abrori (Sekolah tinggi ilmu ekonomi pemuda, 2021)
Village financial management is expected to apply transparency and accountability in its management so that the goals of the central government can be realized properly, in Ketupat village this has not been realized because of the lack of transparency in village financial management towards the community, starting from planning to accountability, this is what happened in Ketupat Village, Raas District, District Sumenep. The purpose of this study was to determine the transparency of village financial management towards the Ketupat Village Community, Raas District, Sumenep Regency. The research method used is descriptive qualitative by describing systematically, factually and accurately about the facts and characteristics that exist in the village administration qualitatively by observing, interviewing directly and in-depth and documenting the transparency of village financial management to the Ketupat village community. Key research informants were the village head, village secretary and treasurer, while the supporting informants were community leaders, village officials and the BPD of Ketupat village. The results showed that the financial management of Ketupat village was not yet transparent to the community, this was revealed from the financial management carried out by the village government both from the planning stage, the implementation stage, the administration stage, the reporting and accountability stages, the lack of involvement of community leaders from each stage of financial management and not. the existence of extension media or information media owned by the village government, including the web, which until now has not been accessible. And there is no good communication between the village government and the BPD of the Ketupat village, Raas sub-district, Sumenep district.